ОПТИМІЗАЦІЯ ТАКТИКИ ВЕДЕННЯ ВАГІТНОСТІ ПІСЛЯ ГРИПУ, ПЕРЕНЕСЕНОГО НА РАННІХ ТЕРМІНАХ ВАГІТНОСТІ (World Science, 2020)
The obtained results created a theoretical basis for optimizing the tactics of pregnancy management in such patients by applying a pathogenetically sound set of treatment and prevention measures. The proposed complex includes assessment of risk factors, additional examinations, monitoring of the condition of the pregnant woman and fetus, treatment measures to prevent placental insufficiency and reduce the negative effects of hyperimmune response (aspirin, dipyridamole, progestogens, intravenous immunoglobulin, vitamin D).To test the effectiveness of the proposed set of treatment and prevention measures, 80 pregnant women were selected after influenza, transmitted in early pregnancy, with a high risk of placental dysfunction. Patients were randomly divided into 2 groups: 40 women whose pregnancies were performed according to optimized tactics (main group) and 40 women (comparison group) whose pregnancies were managed according to the clinical protocols of the Ministry of Health.Testing the effectiveness of the proposed set of measures showed its positive effect on hormonal function of the placenta (normalization of progesterone and estradiol levels), immune status (reduction of NK-cytotoxicity, balance of cytokine profile), elimination of vitamin D deficiency and reduction of procoagulation potential of the hemostasis system.Creating favorable conditions for the development of gestation has reduced the incidence of placental insufficiency by almost 2 times to 35.0% vs. 62.5%. Against the background of the recommended tactics of pregnancy after influenza, the frequency of complications of pregnancy, disorders of the fetus and newborn has decreased significantly.